Handbuch Alttestamentliche Anthropologie - Janowski, Bernd; Dietrich, Jan; Lorenzen, Søren; Grund-Wittenberg, Alexandra; Neumann-Gorsolke, Ute; Wolfs, Rebecca; Wolfs, Rebecca; Grund-Wittenberg, Alexandra; Janowski, Bernd; Neumann-Gorsolke, Ute (Mohr Siebeck, 2023)
Handbook of Old Testament Anthropology.
PublicationDate: 20240228
Keywords: Theologie -- Bibel -- Mensch -- rational choice theory -- Menschenbild -- Nachschlagewerke -- Altes Testament -- Antike -- Array -- Handbuch